A study on the damage tolerance of durable redundant composite sandwich joints. (January 2023) - Goyal, Vinay K; Lundgren, Eric C; Patel, Dhruv N
A patented Durable Redundant Joint (DRJ) concept featuring multiple adhesive load-paths, via a novel composite preform insert, is being considered for joining composite sandwich panel segments. Applications are wide ranging from spacecraft bus structure to launch vehicle primary structure (i.e. interstage cylinders and payload fairings). Numerical and experimental investigations were performed to assess the DRJ's performance. A fracture-based approach was used to evaluate this design. Ply-level mechanical properties for the material systems were generated, and a double cantilever beam coupon was designed and tested to estimate the Mode I critical energy release rate for the interface between two different composite prepreg material systems. The DRJ was tested and compared to testing of the more conventional splice joint (CSJ) design. Polytetrafluoroethylene (PTFE) inserts were used at the free edges of the joints to simulate debonds between the doubler and facesheet laminates. The DRJ coupons reached 32% greater in-plane tensile failure load compared to the CSJ coupons. Furthermore, the predicted increased strength for the DRJ design compared to the CSJ design was in remarkably good agreement with test data. Using the insight gained from these studies, three design attributes were investigated relative to increasing damage tolerance characteristics of the DRJ: (1) Insert stiffness, (2) Relative length between the doubler and the insert, and (3) The use of tapers at the ends of doublers.